Bacterial Communities of Bartonella-Positive Fleas in Gut Microbiota of Armenian Populations - Harutyunyan, N. H.; Manvelyan, A. M.; Balayan, M. H.; Pepoyan, A. Z. (ՀԱԱՀ հիմնադրամ)
Bartonella spp. are known as causative agents of zoonosis. The information on the reservoirs of Bartonella spp. mammals /fleas/ ticks, is limited in Armenia. The aim of this study was, on the basis of the available PhyloChip™data from the previous investigations, to study bacterial communities in healthy and patients with Familial Mediterranean Fever of the Armenian population that have common gene sequences with Bartonella-positive fleas. The preliminary results on PhyloChip™ analysis revealed operational taxonomic units of several gut bacterial communities in healthy people and patients with FMF in the Armenian population sharing common gene-sequences with the Bartonella- positive fleas.
Keywords: Veterinary Science and Animal Breeding